Calculating apparent metabolisable energy (AME) of different oils with and without lysophospholipids for broilers - Jansen van Rensburg, Christine (University of Pretoria, 2018)
With increasing raw material costs, feed formulations are becoming more expensive. Formulating a less energy dense diet and adding an emulsifier to improve lipid digestion and absorption is an option to try and decrease feed costs. Different lipid sources are available on the market but due to their unknown quality it is not always certain what the energy value of the lipid source is and this might lead to over or under supplying of energy to the animal. This study evaluated two commonly used lipid sources in South Africa, soya oil and F10 oil (an unsaturated blend of animal fats and vegetable oils with a maximum of 10% FFA content) which were supplied by Energy Oil (165 Tedstone Road, Wadeville, Gauteng). Both oils were chemically analysed and their AME values were calculated with the Wiseman equation corrected for moisture, impurities and unsaponifiables (MIU), before diets were formulated and the effect of the addition of LYSOFORTE EXTEND dry (LEX) on digestible and performance parameters were investigated. A metabolic study in broilers was conducted to investigate the effect of 2 different oil sources (soya oil and F10 oil) and varying dosage levels of LEX on diet digestibility and apparent metabolisable energy (AME). The study contained 10 treatments: 5 treatments included 3% soya oil and LEX at increasing dosages (0, 0.25, 0.50, 0.75 and 1 g/kg) and 5 treatments included 3% F10 oil and LEX at increasing dosages (0, 0.25, 0.50, 0.75 and 1 g/kg). Diet digestibility parameters were improved for soya oil treatments with the addition of 0.25 g/kg LEX with significant differences for crude protein (CP) digestibility (69.88%), crude fat (EE) digestibility (84.49%) and AME (10.95 MJ/kg). Digestibility parameters for F10 oil treatments were improved with 0.75 g/kg LEX addition, with significant differences for DM digestibility (94.10%) and EE digestibility (84.79%). Following the metabolic study, a 35-day broiler performance trial was conducted to evaluate if the addition of LEX can overcome a 0.42 MJ/kg energy decrease in final feed. The trial included 10 treatments. Five treatments comprised of a basal diet with added soya oil, the positive control contained 3% soya oil (PC) and the negative control (NC) contained 1.8% soya oil with LEX addition at 0, 0.25, 0.50 or 0.75 g/kg, respectively. The other five treatments comprised of a basal diet with added F10 oil, the positive control contained 3% F10 oil (PC) and the negative control (NC) contained 1.8% F10 oil with LEX addition at 0, 0.25, 0.50 or 0.75 g/kg, respectively. Performance parameters including body weight (BW), feed intake (FI) and feed conversion ratio (FCR) were measured weekly during the trial. Growth parameters for both soya oil and F10 oil treatments were improved with the addition of 0.25 g/kg LEX compared to the NC, and this was more noticeable for the F10 oil treatments. A significant difference was noticed for FCR for F10 oil NC (1.63) and F10 oil NC + 0.25 g/kg LEX (1.59) at the end of the 35-day performance period. It was concluded from the metabolic study that an “on top” application of LEX at 0.25 g/kg for a soya oil demonstrated an improved CP digestibility, EE digestibility and AME value for these diets. For diets containing a blended oil an improvement was noticed for DM digestibility, and CF digestibility and AME value when 0.75 g/kg LEX was added. It is recommended to use LEX in an “on top” application at 0.25 g/kg for pure vegetable oils and at 0.75 g/kg for blended oils. For the broiler performance trial, diets were formulated to contain 0.42 MJ/kg less than the PC. Broilers that received soya oil containing diets supplemented with 0.50 g/kg LEX showed a significant improvement in body weight at 28 days of age. Feed conversion ratio at 35 days of age showed a significant with the inclusion of 0.50 g/kg LEX. It is recommended to use LEX in an “on top” application at 0.50 g/kg for both pure vegetable oils and blended oils during commercial broiler farming.